Face Recognition for Classroom Attendance Based on Convolutional Neural Network - Sayyad, Suhel; Mulla , Anis; Gote, Nikita; Bhosale, Pranita; Yadav, Pallavi; Adsul, Ishika (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Marking the attendance of every student manually is a very inconvenient and time consuming task. Our system is based on deep learning architecture to prevent these issues. The automatic attendance system is based on image processing and consists of face recognition, automatically marking a student’s attendance. Face recognition is well studied in computer vision, but it remains unsolved because of pose changes, varying light conditions, and occlusions. Also, teachers spend more time marking each student’s attendance manually. The criteria of minimum time for students in the classroom will be set by the instructor. Our system will monitor the attendance of students through face recognition. As per the timetable’s time and minimum time set by the instructor, student attendance will be marked and stored in the database which will be accessible to the admin.